2018
DOI: 10.1352/1934-9556-56.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences Among Direct Support Professionals

Abstract: Direct support professionals (DSPs) provide integral support to many individuals with intellectual and developmental disabilities (IDD). Yet, individuals' access to qualified DSPs is often compromised as organizations struggle to hire and retain DSPs. Despite a vast body of research exploring factors associated with turnover, adverse childhood experiences (ACEs) among DSPs remain absent from the literature. ACEs encompass abuse and familial dysfunction prior to the age of 18 and, in the general population, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 42 publications
4
37
2
Order By: Relevance
“…Steen (2017) found that among 444 social workers with a history of substance problems, exposure to physical neglect predicted lower levels of career success. Keesler (2018) administered the ACE scale to 386 direct support professionals who worked with individuals experiencing intellectual and developmental disabilities. The study found that ACE scores among these professionals were higher than those reported in the general population.…”
Section: Aces and Social Workersmentioning
confidence: 99%
“…Steen (2017) found that among 444 social workers with a history of substance problems, exposure to physical neglect predicted lower levels of career success. Keesler (2018) administered the ACE scale to 386 direct support professionals who worked with individuals experiencing intellectual and developmental disabilities. The study found that ACE scores among these professionals were higher than those reported in the general population.…”
Section: Aces and Social Workersmentioning
confidence: 99%
“…Exposure to child abuse, family violence, sexual trauma, or alcoholism as a child is linked to unfavorable physical and social outcomes as an adult. ACEs have dose-related effects on adult well-being, indicating more events, the greater the effect (Keesler, 2018). The more adverse events, the higher the risk to adult well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Practically, personal trauma history is worthy of study given its disproportionately high occurrence among mental health workers, as compared with the general population (Keesler, 2018; Lee et al, 2017; Thomas, 2016). For example, Follette et al (1994) found that almost 30% of mental health professionals reported some form of childhood trauma, whereas only 20% of those in law enforcement reported the same, with groups selected due to their exposure to traumatic client material.…”
Section: Key Distinctions Between Work-related Outcomesmentioning
confidence: 99%